2022
DOI: 10.1039/d2na00105e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bactericidal potential and catalytic dye degradation of multiple morphology based chitosan/polyvinylpyrrolidone-doped bismuth oxide nanostructures

Abstract: In this study, 0.02 and 0.04 wt % of chitosan (CS) was successfully incorporated in a fixed amount of polyvinylpyrrolidone (PVP)-doped Bi2O3 nanostructures (NSs) via co-precipitation approach. The purpose of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 86 publications
2
26
0
Order By: Relevance
“…The nanocatalyst surface in the basic medium tends to acquire a negative charge, while the absorption of cationic adsorbate species in acidic media is hindered by the positively charged surfaces of catalysts. 65 The charge on the catalyst surface developed gradually became negative as pH was raised, boosting the adsorption ability of cationic dyes on SnO 2 and GO/PAA-SnO 2 nanocatalysts. The bactericidal potential of pure and doped SnO 2 was evaluated through an agar well diffusion approach.…”
Section: Resultsmentioning
confidence: 99%
“…The nanocatalyst surface in the basic medium tends to acquire a negative charge, while the absorption of cationic adsorbate species in acidic media is hindered by the positively charged surfaces of catalysts. 65 The charge on the catalyst surface developed gradually became negative as pH was raised, boosting the adsorption ability of cationic dyes on SnO 2 and GO/PAA-SnO 2 nanocatalysts. The bactericidal potential of pure and doped SnO 2 was evaluated through an agar well diffusion approach.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Moreover, the CA of SnO 2 is enhanced by adding CS, which is attributed to possessing a large number of active sites. 36 The result indicated that 4% Mg/CS-doped SnO 2 shows optimum (99%) sonophotocatalytic degradation of MB in basic medium compared to photocatalytic and catalytic degradation. From these outcomes, we deduce that SnO 2 QDs proved to be an excellent material for the degradation of the MB dye by the sonophotocatalysis process.…”
Section: Resultsmentioning
confidence: 94%
“…Simultaneously, more dye molecules are absorbed on the surfaces of Mg/CS-doped SnO 2 that enhance dye reduction . Moreover, the CA of SnO 2 is enhanced by adding CS, which is attributed to possessing a large number of active sites . The result indicated that 4% Mg/CS-doped SnO 2 shows optimum (99%) sonophotocatalytic degradation of MB in basic medium compared to photocatalytic and catalytic degradation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[1][2][3] In recent years, inorganic nanomaterials with unique shapes and sizes have received a lot of attention in several fields such as catalysis, dye degradation, and antibacterial properties due to their unique properties. [4][5][6] Among them, the development of various metal oxides including ZnO, [7] Ag 2 O, [8] CuO, [9] TiO 2 , [10] MgO, [11] NiO, [12] and other nanoparticles and their composites has provided more possibilities to explore the antibacterial properties. Additionally, it has been shown that the addition of inorganic nanoparticles can retard the growth of pathogenic bacteria, being of great significance as the active ingredient in food packaging.…”
Section: Introductionmentioning
confidence: 99%